2017
DOI: 10.1515/opag-2017-0063
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary observations on use of Beauveria bassiana for the control of the sweet potato weevil (Cylas sp.) in South Africa

Abstract: Sweet potato weevils (Cylas puncticollis and C. formicarius) are notorious pests of sweet potato and cause severe losses in marketable yield. The study tested the use of Beauveria bassiana ((Balsamo) Vuillemin) (Deuteromycota: Hyphomycetes) for controlling sweet potato weevils. An experiment was conducted using four treatments: 1) dipping sweet potato cuttings in solution of 1 g/litre B. bassiana before planting, 2) spraying with the registered chemical Deltametrin at 50ml/100litre every 2 weeks for four month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…TheC. formicarius assembly genome size is similar to the mean assembly size of the previously published coleopteran genomes (ranging from 110 to 850 Mb) (Hlerema et al , 2017) and is comparable to the genome sizes ofPlastocerus angulosus (367 Mbp) (Kusy, Motyka, Bocek, Vogler, & Bocak, 2018) andHycleus phaleratus (308 Mbp) (Y. M. Wu, Li, & Chen, 2018).…”
Section: Illumina and Pacbio Sequencing And Genome Assemblysupporting
confidence: 81%
See 1 more Smart Citation
“…TheC. formicarius assembly genome size is similar to the mean assembly size of the previously published coleopteran genomes (ranging from 110 to 850 Mb) (Hlerema et al , 2017) and is comparable to the genome sizes ofPlastocerus angulosus (367 Mbp) (Kusy, Motyka, Bocek, Vogler, & Bocak, 2018) andHycleus phaleratus (308 Mbp) (Y. M. Wu, Li, & Chen, 2018).…”
Section: Illumina and Pacbio Sequencing And Genome Assemblysupporting
confidence: 81%
“…Furthermore, the sex pheromone of C. formicarius , (Z)-3-dodecen-1-yl (E)-2-butenoate, was first extracted in 1978 (Coffeltet al , 1978), and the bioactivity of the synthetic compound was tested in both laboratory and field experiments in 1986 (Heath et al , 1986). Olfaction-based approaches, using synthetic sex pheromones to monitor and interfere with the pests' ability to find suitable mates, have been used successfully in "pushpull" control strategies (Hlerema, Laurie, & Eiasu, 2017). However, becauseC.…”
mentioning
confidence: 99%
“…Therefore, control technology to maintain tuber yield is needed, such as the application of innovative technology using the entomopathogenic fungus B. bassiana in this study. The success of controlling tuber borer pests using the fungus B. bassiana was also reported by [20] then [21], which indicated that the application of biopesticides from the entomopathogenic fungus B. bassiana was more effective and efficient in protecting tuber damage due to attack by C. formicarius. Furthermore, [22] confirmed that the biopesticidal efficacy of the entomopathogenic fungus B. bassiana combined with plastic mulch to cover bunds was very significant in suppressing tuber damage by up to 99% of attacks by C. formicarius larvae.…”
Section: Level Of Tuber Damagementioning
confidence: 77%
“…These results could probably be because of the range of sources of origins and genetic history of the genotypes used in this study. Several authors have reported significant cultivar differences among sweetpotato accessions for many important sweetpotato traits (Karan & Sanli, 2021; Gurmu et al., 2018; Hlerema et al., 2017; Muyinza et al., 2012; Mwanga et al., 2003; Stathers, Rees, Kabi et al., 2003; Stathers, Rees, Nyango et al., 2003). Earlier on, farmers from the major sweetpotato growing districts (Masindi, Kasese, Kabale, Wakiso, Soroti, and Gulu) in Uganda identified six sweetpotato land races that they grow to be resistant to the Cylas spp.…”
Section: Discussionmentioning
confidence: 99%